Indonesia’s Regional Elections : Ditching the Direct Vote? - Dinarto, Dedi (2020)
Indonesia’s newly appointed Minister of Home Affairs has decisively called for a major review of the direct election of regional leaders. While this signals the ministry’s growing clout, the institution is likely to involve active military and police officers to fill the impending vacuum in key regional leadership positions from 2022 to 2024. There are challenges ahead.